Analysis of Kwesimintsim Polyclinic Health Data - Baah, Emmanuel Mensah (University of Cape Coast, 2004)
This dissertation is a report on efforts directed at finding the leading diseases, patterns and other characteristics of four kinds of data: Monthly Outpatient Morbidity Data, Statement of Outpatients, Statement of Inpatients and the Monthly Bed State Data of Kwesimintsim Polyclinic. The data spans the six-year period of 1997 to 2002. The analysis of the data relied on descriptive statistics and time series analysis. Projected values of the number of cases of the diseases to be reported to the Polyclinic, particularly that of malaria in the immediate future were also explored. Analysis of the data showed that Malaria is the leading of the 13 most common diseases in the catchment area with an upward trend in the number of cases reported at the Polyclinic. It was also found that the number of cases of Pneumonia and Hypertension are on the ascendancy while tuberculosis is the most prevalent of the 'Six Child killer Diseases' Diphtheria, Poliomyelitis, Tetanus, Measles, Whooping Cough, and Tuberculosis in the catchment area. Further, Females and the age group 0-4 years are the subgroups in the population of the catchment area that require the most medical attention.
vii, 76p:,ill.
Keywords: Kwesimintsim Polyclinic; Diseases; Data